2013
DOI: 10.1371/journal.pone.0077638
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Induces Sensitization to Gluten in Genetically Susceptible Individuals: A Case Control Study

Abstract: BackgroundThe mechanisms of cerebellar degeneration attributed to prolonged and excessive alcohol intake remain unclear. Additional or even alternative causes of cerebellar degeneration are often overlooked in suspected cases of alcohol-related ataxia. The objectives of this study were two fold: (1) to investigate the prevalence of gluten-related serological markers in patients with alcohol-related ataxia and; (2) to compare the pattern of brain involvement on magnetic resonance imaging between patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Yet the aetiology of cerebellar degeneration in the context of excessive alcohol intake remains obscure. The toxic effect of alcohol on the cerebellum is a factor but genetic and autoimmune predisposition may contribute 6 19…”
Section: Discussionmentioning
confidence: 99%
“…Yet the aetiology of cerebellar degeneration in the context of excessive alcohol intake remains obscure. The toxic effect of alcohol on the cerebellum is a factor but genetic and autoimmune predisposition may contribute 6 19…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that cerebellar neuronal physiology is abnormal in patients with GA even in the absence of cerebellar structural deficit and that MR spectroscopy may prove a useful tool for monitoring disease. However, more recent work has indicated that the MR spectroscopy was only statistically abnormal compared to controls from the vermis which also reflects the pattern of atrophy seen, which affects the vermis earlier and more severely than the hemispheres [48, 49]. There is no published longitudinal evidence of the use of MR spectroscopy for follow up of patients with GA.…”
Section: Section 5: Imaging In Immune-mediated Ataxiasmentioning
confidence: 99%
“…Proposed mechanisms for the high prevalence of TG2 autoantibodies in patients with chronic alcohol abuse include increased gut permeability associated with alcohol induced intestinal mucosal lesions [ 9 ] leading to increased exposure of the immune system to pathogenic antigens (including gluten peptides). In line with this, alcohol has been shown to induce sensitisation to gluten in genetically susceptible individuals [ 12 ].…”
Section: Introductionmentioning
confidence: 92%